The transcriptional regulation effects of histidine, isoleucine and glutamate on free exopolysaccharide biosynthesis of Streptococcus thermophilus 937 - Wa, Yunchao; Zhao, Xia; Zhang, Chenchen; Qu, Hengxian; Chen, Dawei; Chen, Xia; Huang, Yujun; Gu, Ruixia (Frontiers in Microbiology, 2025)
IntroductionThe free exopolysaccharide (f-EPS) produced by Streptococcus thermophilus is a natural texture modifier and has a variety of prebiotic activities. Our previous studies showed f-EPS production from S. thermophilus 937 was increased 2-fold in the presence of 15 mM of glutamate, isoleucine, and histidine in the chemically defined medium.MethodsIn this study, we used transcriptomics and qPCR to further explore the specific mechanism of the enhanced effect of 3 amino acids on the f-EPS biosynthesis of S. thermophilus 937.ResultsThe mRNA-seq analysis and targeted pathway analysis indicated that genes associated with histidine/valine/leucine/ isoleucine/phenylalanine/tyrosine/tryptophan synthesis, galactose metabolism, purine metabolism and quorum sensing in S. thermophilus 937 were significantly upregulated under increasing concentrations of histidine, isoleucine and glutamate in chemically defined medium (CDM). qPCR results showed that the significant upregulation of galactose metabolism- and nucleotide sugar synthesis-related genes was attributed to the increase in glutamate concentration, and glutamate could induce the expression of galR. The upregulation of epsA, epsB, and epsD transcript levels was caused by the increase in histidine concentration. The upregulation of transcript levels of genes related to phenylalanine/tyrosine/tryptophan/histidine/ valine/leucine/isoleucine synthesis was caused by the increase in isoleucine concentrations.DiscussionThis indicates that 3 amino acids have different mechanisms for enhancing the biosynthesis of f-EPS in S. thermophilus 937.